1995
DOI: 10.1123/pes.7.2.132
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Children’s Physical Self-Perceptions Using an Adapted Physical Self-Perception Profile Questionnaire

Abstract: This project was a study of the validity and reliability of adapted versions of Fox and Corbin’s (10) Physical Self-Perception Profile (PSPP) and Perceived Importance Profile (PIP) for use with seventh- and eight-grade students. The Children’s PSPP and PIP (C-PSPP and C-PIP) questionnaires were completed by 505 students. Results supported the reliability and the construct and concurrent validity of the C-PSPP scales. Factorial validity of the C-PIP was not demonstrated. Similar to Fox and Corbin’s (10) results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
185
2
23

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(225 citation statements)
references
References 0 publications
15
185
2
23
Order By: Relevance
“…36 Dimensions of physical appearance, close friendship, athletic competence, social acceptance, romantic appeal, and global self-worth were included in the current study. The children's physical self-perception profile (CPSPP) 37 was used to provide an additional assessment of self-concept related to physical appearance. Social support was measured using the social support scale for children and adolescents (SSSCA).…”
Section: Methodsmentioning
confidence: 99%
“…36 Dimensions of physical appearance, close friendship, athletic competence, social acceptance, romantic appeal, and global self-worth were included in the current study. The children's physical self-perception profile (CPSPP) 37 was used to provide an additional assessment of self-concept related to physical appearance. Social support was measured using the social support scale for children and adolescents (SSSCA).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, SPORT, COND, BOBY, and STREN scores explained a high percentage of the variance in the overlying construct of PSW which mediated the relationship of these four subdomain subscale scores with global self-esteem. Whitehead (1995) adopted the PSPP to use it for children and adolescents. The C-PSPP (Whitehead, 1995) consisted of three of the original PSPP (Fox & Corbin, 1989) subscales (i.e., COND, BOBY, and STREN) and Harter's (1982) sport competence subscale that was almost identical to the corresponding PSPP scale and already validated.…”
Section: Introductionmentioning
confidence: 99%
“…Whitehead (1995) adopted the PSPP to use it for children and adolescents. The C-PSPP (Whitehead, 1995) consisted of three of the original PSPP (Fox & Corbin, 1989) subscales (i.e., COND, BOBY, and STREN) and Harter's (1982) sport competence subscale that was almost identical to the corresponding PSPP scale and already validated. Moreover, the C-PSPP included a global PSW (Whitehead & Corbin, 1991) and a general GSW (Harter, 1982) scale.…”
Section: Introductionmentioning
confidence: 99%
“…[34]. In a study looking at health-related Quality of Life, overweight and obese adolescents reported significantly lower scores compared to their healthy counterparts [35].…”
Section: Prompt Self-talkmentioning
confidence: 99%